2010
DOI: 10.1002/em.20570
|View full text |Cite
|
Sign up to set email alerts
|

The approaches for manipulating mitochondrial proteome

Abstract: Over the past decade a large volume of research data has accumulated which has established a fundamental role for mitochondria in normal cellular functioning, as well as in various pathologies. Mitochondria play a pivotal role in metabolism and energy production, and are one of the key players involved in programmed cell death. On the other hand, mitochondrial dysfunction is implicated, directly or indirectly in numerous pathological conditions including inherited mitochondrial disorders, diabetes, cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…A third approach is genetic; for example, Tann et al (2011) recently used siRNA to specifically deplete the mtDNA repair enzyme ExoG, Green et al (2011) studied the effects of p53 deficiency on cellular response to rotenone, and Simsek et al (2011) compared the rescue capacity of nuclear- versus mitochondrial-targeted DNA Ligase III in DNA Ligase III–deficient mice. Several groups have demonstrated mtDNA-mediated effects by targeting DNA repair enzymes to mitochondria, improving DNA repair, and reducing or rescuing the toxic effects observed (Cai et al ., 2005; Koczor et al ., 2009; Rachek et al ., 2009; Shokolenko et al ., 2010). The use of a suite of toxicants that all impact a similar mitochondrial target (e.g., ETC complex I) has also been employed (Kulawiec et al ., 2009).…”
Section: Mitochondrial Susceptibility To Environmental Toxicantsmentioning
confidence: 99%
“…A third approach is genetic; for example, Tann et al (2011) recently used siRNA to specifically deplete the mtDNA repair enzyme ExoG, Green et al (2011) studied the effects of p53 deficiency on cellular response to rotenone, and Simsek et al (2011) compared the rescue capacity of nuclear- versus mitochondrial-targeted DNA Ligase III in DNA Ligase III–deficient mice. Several groups have demonstrated mtDNA-mediated effects by targeting DNA repair enzymes to mitochondria, improving DNA repair, and reducing or rescuing the toxic effects observed (Cai et al ., 2005; Koczor et al ., 2009; Rachek et al ., 2009; Shokolenko et al ., 2010). The use of a suite of toxicants that all impact a similar mitochondrial target (e.g., ETC complex I) has also been employed (Kulawiec et al ., 2009).…”
Section: Mitochondrial Susceptibility To Environmental Toxicantsmentioning
confidence: 99%
“…However, a number of therapeutic approaches have been already applied or are still under development (15,26,(47)(48)(49)(50)(51). Some of these approaches are indicated below.…”
Section: Mitochondrial Medicinementioning
confidence: 98%
“…Furthermore, MTD-TFAM fusion protein improved motor function in mice treated with MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine), which is able to induce experimental parkinsonism (178). Wilson's group (49,179) used an MTS (from the human MnSOD mitochondrial protein) to target the DNA repair enzyme Exonuclease III (ExoIII) into the mitochondria of breast cancer cells via the PTD technology. The goal of this strategy was to sensitize these cells to oxidative stress in the general frame of increasing the mtDNA's repair capacity.…”
Section: Ptd-mediated Protein Replacement Therapy (Prt) As a Therapeumentioning
confidence: 99%
“…Recent findings showed that mitochondrial genome can be manipulated from outside the cell in order to alter its expression and increase mitochondrial energy production [178]. Mitochondrial genome exploitation can include overexpression of nuclear-encoded mitochondrial proteins, allotopic expression, which comprises the recoding and transfer of mitochondrial genes to the nucleus for expression and delivery of their products to mitochondria, and xenotopic expression, the nuclear expression of genes encoding ETC machinery from distant species and posterior delivery to mammalian mitochondria [179]. Iyer et al [178] developed a scalable procedure to produce human Tfam modified with an N-terminal protein transduction domain and mitochondrial localization signal that allow it to cross membranes and enter mitochondria through its "mitochondrial transduction domain" (MTD).…”
Section: Impaired Mitochondrial Biogenesismentioning
confidence: 99%